ANALISYS OF FACTORS AFFECTING USER SATISFACTION OF INSTITUTION LEVEL FINANCIAL APLICATION SYSTEM AND ITS INFLUENCE ON INFORMATION SYSTEM BENEFITS - Richard; Amiruddin; Syamsuddin (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to analyze the extent to which the acceptance and success of implementing the Financial Application System at the Agency Level (SAKTI) and identify the factors that influence User Satisfaction and their impact on the Benefits of Information Systems with the Unified Theory of Acceptance and Use of Technology (UTAUT) Model approach and The DeLone and McLean Information Systems Success Model. This research is a causal explanatory research with a quantitative approach. Primary data was obtained through questionnaires from 237 SAKTI users who were in the working area of the Kupang KPPN , East Nusa Tenggara Province . SmartPLS is used to analyze the data. Hypothesis testing shows that Performance Expectancy, Service Quality, and Interaction Design Quality have a positive effect on User Satisfaction. Likewise, User Satisfaction has a positive effect on the Benefits of Information Systems at the organizational level.